ANALISIS STUDI KELAYAKAN USAHA PENDIRIAN HOME INDUSTRY (STUDI KASUS PADA HOME INDUSTRI "OLLANDA BROWNIES" PANAM PEKANBARU) - Syahsudarmi, Siti (Eko dan Bisnis: Riau Economic and Business Review, 2020)
Brownis home industry â€œollandaâ€ is a new bussines that was founded with is own capital, which is equel to Rp 28.028.000 . The produck produced in the form of brownis with various flavors. This study aims to determine the level of investment of a home industryÂ  brownis â€œollandaâ€ which is lacated Jl. HR. Soebrantas Panam No. 73D, Tuah Karya, kec. Tampan, Pekanbaru City, Riau 28291. This research was conducted in February 2020 with data collection techniques in the form of observation, interviews and dokumentotion. The methods used are market and marketing aspect, engineering aspect and production aspect . organizational and management aspect as well as financial aspect with investment feasibility calculation in the form of payback period(PP), Net Present Value (NPV), Internal RateÂ  of Return (IRR), and Profitability Index( PI). Market and marketing analysis shows that the prospect of the â€œollandaâ€ brownis home industry is quite good, seen from the increasing number of requests every year. Technical analysis of production show that the lacation of the home industry is close to settlements making it easier to recruit workers. Analisis of organizational and management personal show that bussines oners have carried out management functions well.